(untitled) (Semiárida, 2020)
Standing crop of a Pappophorum caespitosum "pasto blanco" grassland was determined in the southeastern of La Pampa Province, Dpto. Caleu Caleu, Ea. Los Guadales. Lat. 38°13’S Long. 64°18’ W. At the end of autumn (June) the grassland reached 310 gMS/m2 Pappophorum caespitosum, the principal specie totalized 224 gMS/m2. In spring (October) Medicago minima "Trébol de carretilla" y Erodium cicutarium "alfilerillo", two annual species gave 248 gMS/m2. The vegetation cover was high in the grassland during all the year. "Pasto blanco" had 100% of annual frequency and "Trébol de carretilla" y "alfilerillo" the 90%.